Fraxetin suppresses reactive oxygen species‐dependent autophagy by the PI3K/Akt pathway to inhibit isoflurane‐induced neurotoxicity in hippocampal neuronal cells. Issue 4 (22nd September 2021) - Zhang, Tongyin; Zhou, Botao; Sun, Junyi; Song, Jiangling; Nie, Limin; Zhu, Kairun
Abstract: Isoflurane, a common volatile anesthetic, has been widely used to provide general anesthesia in operations. However, exposure to isoflurane may cause widespread neurotoxicity in the developing animal brain. Fraxetin, a natural coumarin derivative extracted from the bark of Fraxinus rhynchophylla, possesses versatile pharmacological properties including anti‐oxidative, anti‐inflammatory, and neuroprotective effects. However, the effect and action mechanism of fraxetin on neurotoxicity induced by isoflurane are unknown. Reactive oxygen species (ROS) generation, cell viability, lactate dehydrogenase (LDH) release, and apoptosis were estimated by 2′, 7′‐dichlorofluorescin‐diacetate (DCFH‐DA) staining, MTT, LDH release, and terminal deoxynucleotidyl transferase‐mediated deoxyuridine triphosphate nick end‐labeling (TUNEL) staining assays, respectively. The protein levels of light chain 3 (LC3)‐I, LC3‐II, p62, protein kinase B (Akt), and phosphorylated Akt (p‐Akt) were detected by western blot analysis. Isoflurane induced ROS, LDH release, apoptosis, and autophagy, but inhibited the viability in HT22 cells, which were overturned by fraxetin or ROS scavenger N‐acetyl‐L‐cysteine. Fraxetin suppressed isoflurane‐induced PI3K/Akt inactivation in HT22 cells. PI3K/Akt inactivation by LY294002 resisted the effects of fraxetin on isoflurane‐induced autophagy and autophagy‐modulated neurotoxicity in HT22 cells. In conclusion, fraxetin suppressed ROS‐dependent autophagy by activating the PI3K/Akt pathway to inhibit isoflurane‐induced neurotoxicity in hippocampal neuronal cells. Abstract : Exposure to isoflurane may cause neurotoxicity. Fraxetin possesses neuroprotective effects. However, the effects and mechanisms of fraxetin on isoflurane‐induced neurotoxicity are unknown. We found that fraxetin or reactive oxygen species (ROS) scavenger N‐acetyl‐L‐cysteine overturned isoflurane‐induced neurotoxicity and autophagy. Fraxetin suppressed isoflurane‐induced PI3K/Akt inactivation. PI3K/Akt inactivation by LY294002 resisted the effects of fraxetin on isoflurane‐induced autophagy and autophagy‐modulated neurotoxicity in HT22 cells. Summarily, fraxetin suppressed ROS‐dependent autophagy by activating the PI3K/Akt pathway to inhibit isoflurane‐induced neurotoxicity.